2014
DOI: 10.1186/1999-3110-55-5
|View full text |Cite
|
Sign up to set email alerts
|

Karyological, morphological and phytochemical characteristics of medicinal plants Sophora flavescens Aiton grown from seeds collected at different localities

Abstract: BackgroundDried roots of Sophora flavescens Aiton contain many phytochemicals that exhibit beneficial effects on human health. This study examined and compared the karyological, morphological and phytochemical characteristics of three S. flavescens populations collected from the Danda, Hualien and Yuli of Taiwan and a population collected from Gansu, China.ResultsKaryotypes of the four populations were similar, with a diploid number of 2n = 18. The Hualien population produced more roots but with less matrine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The contact map of Hi-C interaction for our S. flavescens genome assembly revealed nine chromosomal level scaffolds, which is consistent with the reported S. flavescens karyotype (Fig. 1d) 30 , indicating the high contiguity of the genome assembly. With respect to the completeness of the genome assembly, the BUSCO analysis with lineage "fabales_odb10" showed that 93.3% of Fabales gene orthologs could be identified in this S. flavescens genome assembly, including complete and fragment percentages of 91.3% and 2.0%, respectively (Table 1).…”
Section: Technical Validationsupporting
confidence: 89%
“…The contact map of Hi-C interaction for our S. flavescens genome assembly revealed nine chromosomal level scaffolds, which is consistent with the reported S. flavescens karyotype (Fig. 1d) 30 , indicating the high contiguity of the genome assembly. With respect to the completeness of the genome assembly, the BUSCO analysis with lineage "fabales_odb10" showed that 93.3% of Fabales gene orthologs could be identified in this S. flavescens genome assembly, including complete and fragment percentages of 91.3% and 2.0%, respectively (Table 1).…”
Section: Technical Validationsupporting
confidence: 89%
“…These nine scaffolds most likely correspond to the nine chromosomes of S. flavescens (Fig. 1d) Lin et al (2014). The BUSCO assessment of the final draft genome indicated that 4,898 of the 5,366 (91.3%) Fabales BUSCO groups were complete, with 86.7% and 4.6% as single-copy and duplicated BUSCOs respectively (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…These nine scaffolds most likely correspond to the nine chromosomes of S. flavescens (Fig. 1d) Lin et al (2014).…”
Section: Chromosomal Level Draft Genome Assembly Of S Flavescensmentioning
confidence: 99%
“…Relatively little is known about the extent of genetic and phenotypic diversity in S. flavescens . In a study of plants from four locations (three in China and one in Taiwan), Lin et al (2014) established that the plants were diploid (2 n = 18) and observed statistically significant variation in biochemical composition (matrine, oxymatrine, flavonoids, and antioxidants) and 11 morphological traits among field-grown plants.…”
Section: Introductionmentioning
confidence: 99%